The Impact of Financial Literacy, Digital Financial Adoption, Access to Credit, and Risk Perception on SMEs Financial Performance - Sekamdo, Muhammad Aga; Rijal, Syamsu (International Journal of Business, Law, and Education, 2026)
Small and Medium-sized Enterprises (SMEs) remain important in the process of economic development, although many continue to struggle with sustainable financial performance. In this study, the research focus is on the role of financial literacy, adoption of digital financial services, credit availability, and risk perceptions in determining the financial performance of SMEs in the market. In this study, the research methodology is based on a quantitative design, with the goal of establishing the relationship and the extent to which the variables influence the financial performance of SMEs in the market. In this research study, the data is set to be collected through the use of a structured research questionnaire, the respondents for whom are the owner and manager of the small and medium-scale enterprises in the market. By the use of the research methodology, the results of the research study found that financial literacy, adoption of digital financial services, and credit availability have a significant relationship with the financial performance of SMEs in the market, although risk perceptions have a negative relationship with the financial performance of the entities in the market. In the research study, financial.